(untitled) (Development Service Industry Management, 2023)
The article reveals the relevance of strategic marketing, namely the formation and implementation of marketing tools to ensure the strategic development of business entities. The purpose of the study is to improve the theoretical, methodological and applied principles of management of marketing tools in the field of strategic development of business entities. It has been proven that strategic marketing plays an important role in the design of stable long-term functioning and development of business structures. The components of the combination of marketing and strategic planning of the development of business structures have been identified, namely, defining the mission of the enterprise, substantiating strategic marketing tasks, placing resources, implementing key strategic efforts, defining and achieving marketing goals and tasks of business in relation to consumers, realizing business goals in relation to its competitors, maximizing competitive advantages, effective use of marketing tools (marketing mix), policy implementation and control. The vectors of strategic development of business structures and marketing elements that determine them are indicated. These are: (1) increasing the volume of activity, (2) increasing the efficiency of management. The role of marketing in their follow-up is also significant when the leading policy objects of business structures become: market expansion, deeper market penetration, optimization and cost reduction, price increase and improvement of price policy, improvement of the system of product sales promotion (providing services) of the enterprise in the markets. It was established that the most important task in the system of the marketing component of the strategic development of business structures is the determination of the provisions and implementation of the tasks of the marketing competitive strategy, which depends on the ability of the business to adapt to the market and market competition, to use its advantages and weaken the weak points, thus guaranteeing a stable and permanent long-term functioning and development. The leading strategies are: (1) development strategy, (2) balancing strategy, (3) protection and preservation strategy.